Structure of the PTEN-like region of auxilin, a detector of clathrin-coated vesicle budding - Guan, Rong (2010)
Auxilin, a J-domain containing protein, recruits the Hsc70 uncoating ATPase to newly budded clathrin-coated vesicles. The timing of auxilin arrival determines that uncoating will commence only after the clathrin lattice has fully assembled and after membrane fission is complete. Auxilin has a region resembling PTEN, a PI3P phosphatase. We have determined the crystal structure of this region of bovine auxilin 1; it indeed resembles PTEN closely. A change in the structure of the P-loop accounts for the lack of phosphatase activity. Inclusion of phosphatidylinositol phosphates substantially enhances liposome binding by wild-type auxilin, but not by various mutants bearing changes in loops of the C2 domain. Nearly all these mutations also prevent recruitment of auxilin to newly budded coated vesicles. We propose a specific geometry for auxilin association with a membrane bilayer and discuss implications of this model for the mechanism by which auxilin detects separation of a vesicle from its parent membrane.